Productive potential and quality of pitaya with nitrogen fertilization - Deilson de Almeida Alves; Maria do Céu Monteiro Cruz; João Esdras Lima; Núbia Cassiana Santos; Josimara Mendes Rabelo; Fernanda de Lima Barroso (Pesquisa Agropecuária Brasileira, 2021)
Abstract The objective of this work was to determine adequate rates of nitrogen to reach satisfactory yield, fruit quality, and cladode nutrient content in three species of pitaya. The experimental design was carried out in randomized complete blocks, with a 3×4 factorial arrangement. The treatments consisted of the following pitaya species and N rates: Selenicereus megalanthus, Hylocereus undatus, and Hylocereus polyrhizus; and 0, 50, 100, and 200 g N per plant, in the first production cycle (2016/2017 crop season) and 50, 100, 200, and 300 g N per plant, in the second and third production cycles (2017/2018 and 2018/2019 crop seasons). Nitrogen fertilization increased the yield, fruit quality, and cladode nutrient content of the species. In the third production cycle, yield was 1.18 Mg ha-1 for S. megalanthus, 10.87 Mg ha-1 for H. undatus, and 10.4 Mg ha-1 for H. polyrhizus in open pollination. The highest yield is obtained with 300 g N per plant for S. megalanthus. For H. polyrhizus and H. undatus the rates are from 170 to 190 g N per plant, supplemented with P and K.